PEMBELAJARAN RELASI DAN FUNGSI DENGAN MODEL BLENDED LEARNING - Sylvia Jane Sumarauw; Claudi Gabriel Kaligis; Victor Sulangi (Discovery : Jurnal Ilmu Pengetahuan, 2022)
In relation and function material, student learning outcomes are low. One of the various innovative and effective learning models that can be used is the Blended Learning model. This study aims to describe the learning outcomes of class VIII SMP Tridharma Manado in relation and function using the face-to-face learning model which is lower than the student learning outcomes using the Blended Learning model. Class VIII A is the research subject and as the experimental class (the class that applies the Blended Learning model) consisting of 23 students and class VIII B as the control class (the class that uses the face-to-face learning model) consisting of 23 students. In this study, the instrument is a test in the form of description questions to measure student learning outcomes. Posttest is a data collection technique used in this study; in the form of a description question consisting of 5 questions. By using t-test statistics, the results of hypothesis testing are obtained where tcount = 2,593 > ttable = 1,680, thus the average student learning outcomes using the Blended Learning model are higher than student learning outcomes using the face-to-face learning model.